PREVALENSI ASMA EKSASERBASI PADA IBU HAMIL DAN PENGARUHNYA TERHADAP JANIN DAN IBU DI RSUP SANGLAH DENPASAR - Ngurah Rai, I B (journal of internal medicine; Vol. 10, No. 3 September 2009)
The prevalence of asthma among pregnant females is increasing. Asthma is one of the most common chronic medical conditions that cause complications in pregnancy. There is evidence that asthma can adversely impact on pregnancy outcomes, and conversely that pregnancy may result in a change in the clinical status of a female with asthma. The aim this study was to know prevalence of asthma exacerbation in pregnancy and the effects to infant and maternal in Sanglah General Hospital. This study is retrospective study to medical record of pregnancy patients delivery at Sanglah General Hospital. In this study we found 1959 pregnancy patients and prevalence of asthma exacerbation was 0.71% (14 asthmatic patients) Proportion of pathologic delivery, pre-eclampsia and congenital malformations of the fetus was lower in asthmatic group than in group without asthma but not signi! cant. The mean of birth weight was lower in asthma group than in group without asthma (3107.14 ± 521.78 grams : 3306.70 ± 366.21 grams) p = 0.05 95%CI (-399.14 ? 0.012). The conclusion this study is prevalence of asthma exacerbations on pregnant females in Sanglah General Hospital was 0.71%. Birth weight both in pregnant females with asthma and pregnant females without asthma was in normal limit but trend was lower in pregnant females with asthma than pregnant females without asthma.
Keywords: asthma exacerbation, pregnancy, Sanglah hospital